The Well-Woman Project: Listening to Women's Voices - Arden Handler; Vida Henderson; Regan Johnson; Cristina Turino; Megan Gordon; Megan Franck; Nadine Peacock; Denise Pecha (Mary Ann Liebert, 2019)
Purpose: The U.S. Affordable Care Act (ACA) of 2010 included the Well-Woman Visit (WWV) as one of the preventive services, which must be covered without cost sharing. Despite concerted efforts to increase access to the WWV, data from the early years of the ACA demonstrated ongoing barriers, including insufficient consumer and provider awareness of the ACA's no cost-sharing provision for preventive services. As such, 2 years after full implementation of the ACA, the Well-Woman Project (WWP) used qualitative methods to learn about women's perceptions of the WWV and barriers that affect their ability to be healthy and seek well-woman care. Methods: Women's voices were captured by Listening Sessions in eight cities and through stories from women across the United States posted to a WWP Website, or reported over a WWP toll-free phone line. Thematic analysis of Listening Sessions and stories was conducted using Dedoose software. Results: In 2016, Listening Sessions (17) were held with 156 women; in addition, stories were collected from 102 women across the United States. Women are aware of the importance of preventive care, but report multiple barriers to seeking such care. However, they are able to articulate a variety of system and policy strategies that mitigate the complexity of navigating the health care system; help women prioritize their health and accessing health care; promote positive relationships with providers; empower women to advocate for themselves and others; promote positive mental health as well as access to safe environments, healthy food, and social support systems; decrease barriers related to lack of transportation and childcare; and support the provision of trauma informed care in the health care delivery system. Conclusion: To improve women's health status and reduce inequities, making the preventive well-care visit available without cost-sharing is necessary, but not a sufficient strategy.